Perceived HRD Practices and Employee Performance - An Empirical Study of Select Private Engineering Colleges in Hyderabad - Venkataiah, Ch. (Prabandhan: Indian Journal of Management, 2011)
A number of studies have been conducted on the relationship between HRD practices and employee performance. Small evidence is available about a relationship between HRD practices and employee performance from developing countries like India. This study examines the association between three HRD practices, i.e. compensation, promotion, performance evaluation, and perceived employee performance among teachers working in private engineering educational institutions in Hyderabad region. The results of the study indicate a positive relationship between compensation, promotion practices, and employee perceived performance, while performance evaluation practices are not significantly correlated with perceived employee performance. Private engineering educational institutions need to revise compensation practices and define clear career paths to enhance the performance of teachers.